CK‐2127107 amplifies skeletal muscle response to nerve activation in humans. Issue 5 (11th December 2017) - Andrews, Jinsy A.; Miller, Timothy M.; Vijayakumar, Vipin; Stoltz, Randall; James, Joyce K.; Meng, Lisa; Wolff, Andrew A.; Malik, Fady I.
ABSTRACT: Introduction: Three studies evaluated safety, tolerability, pharmacokinetics, and pharmacodynamics of CK‐2127107 (CK‐107), a next‐generation fast skeletal muscle troponin activator (FSTA), in healthy participants. We tested the hypothesis that CK‐107 would amplify the force‐frequency response of muscle in humans. Methods: To assess the force‐frequency response, participants received single doses of CK‐107 and placebo in a randomized, double‐blind, 4‐period, crossover study. The force‐frequency response of foot dorsiflexion following stimulation of the deep fibular nerve to activate the tibialis anterior muscle was assessed. Results: CK‐107 significantly increased tibialis anterior muscle response with increasing dose and plasma concentration in a frequency‐dependent manner; the largest increase in peak force was ∼60% at 10 Hz . Discussion: CK‐107 appears more potent and produced larger increases in force than tirasemtiv—a first‐generation FSTA—in a similar pharmacodynamic study, thereby supporting its development for improvement of muscle function of patients. Muscle Nerve 57 : 729–734, 2018